The properties of concrete containing coconut shell as part of coarse aggregate replacement - Hafiz Osman, Mohammad (2017)
The demand of concrete in the construction industry increased rapidly due to continuous development in Malaysia. Extensive use of concrete leads to sacristy of natural aggregates. The reuse solid waste from manufacturing is an alternative way to preserve waste management problem as well as to reduce the depletion of natural resources. This study was conducted to investigate the flexural strength and compressive strength of the concrete with coconut shell replacement as coarse aggregate. In this study, coconut shell was used to partial replace the coarse aggregate by 5%, 10% and 15%. All concrete was design to grade C25 / 30 and all samples cured for 7days, 14days and 28days. Test compressive strength and flexural strength conducted to determine the strength of hardened concrete. The result presented that 15% coconut shell replacement in concrete by compressive strength and flexural strength higher than the replacement of 5% and 10%. The results showed coconut shell can be used in concrete construction.